Low-temperature sintering of Ba(Zr,Y)O-3-based proton conducting oxides using BaO-CuO eutectic flux as sintering aid - Biswas, Mridula; An, Hyegsoon; Choi, Sung Min; Son, Ji-Won; Lee, Jong-Ho; Kim, Byung-Kook; Lee, Hae-Weon; Yoon, Kyung Joong (ELSEVIER SCI LTD, 2016)
The major barrier to the practical application of Ba(Zr,Y)O-3 (BZY) as an electrolyte material for proton conducting fuel cells (PCFCs) lies in its extremely inferior sintering characteristics. In this research, flux composed of 28 mol% BaO and 72 mol% CuO was employed as a novel sintering aid for BZY. Incorporation of nano-crystalline BaO-CuO flux, with a eutectic point of 890 degrees C, remarkably enhanced the sintering behavior of BZY due to the formation of a transient liquid phase, and a relative density of up to 97% of the theoretical density was obtained at 1300 degrees C with a short soaking time of 2 h. (C) 2016 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: DOPED BARIUM ZIRCONATE; ELECTRICAL-CONDUCTIVITY; CHEMICAL-STABILITY; FABRICATION; CALCIUM; POWDERS; DECOMPOSITION; ELECTROLYTE; PERFORMANCE; STRONTIUM